The DNA Methylation Inhibitor Zebularine Controls CD4+ T Cell Mediated Intraocular Inflammation - Zou, Yanli; Hu, Xiao; Schewitz-Bowers, Lauren P.; Stimpson, Madeleine; Miao, Li; Ge, Xiaofei; Yang, Liu; Li, Yan; Bible, Paul W.; Wen, Xiaofeng; Li, Jing Jing; Liu, Yizhi; et al. (Frontiers in Immunology, 2019)
CD4+ T cell mediated uveitis has been treated with corticosteroids, immunosuppressive agents, and biologics targeting key inflammatory cytokines. However, many patients are resistant or intolerant to current therapies. Here, we investigated whether DNA methylation inhibitor zebularine can target CD4+ T cells and control intraocular inflammation. Our results showed that zebularine restrained the expression of inflammatory cytokines IFN- and IL-17 in both human and murine CD4+ T cells in vitro. Importantly, it also significantly alleviated intraocular inflammation and retinal tissue damage in the murine experimental autoimmune uveitis (EAU) model in vivo, suggesting that DNA methylation inhibitor zebularine may be a potential therapeutic agent for uveitis treatment.